Investigating self-concept in EFL pronunciation among Chinese Non-English major learners at a public university in China - Asmaa AlSaqqaf; Zhang Xin; Sabariah Sharif (Asian Economic and Social Society (AESS), 2023)
Very limited research has explored the English pronunciation and self-concept among EFL non-English major learners in China. Therefore, this study investigated the level of Chinese EFL non-English major learners’ self-concept about their level of English pronunciation, how they self-evaluated their English pronunciation, and the pronunciation problems they encountered. A convergent mixed-method approach was utilized to collect data. A sample of 392 Chinese EFL learners from different universities responded to an English pronunciation questionnaire about self-concept, where results showed that Chinese EFL non-English major learners had a very low self-concept of English pronunciation. Meanwhile, another sample of 100 students took an English pronunciation test and responded to the English pronunciation self-evaluation form. Results demonstrated that 82% of the participants scored 59/100 and below in the English pronunciation test. As for the self-evaluation of English, also 82% self-evaluated their English as either average or poor. Moreover, a focused group discussion with five EFL teachers showed that among the pronunciation problems faced by Chinese EFL learners included: a) adding or omitting extra sounds, b) problems with phonemes, c) confusion of vowels and consonants, and d) problems with suprasegmental phonemes. It is hoped that this study would provide some implications for putting forward countermeasures to improve the EFL pronunciation among EFL Chinese learners.